2022
DOI: 10.3390/nu14020383
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Nutritional Status and Sarcopenia in Pediatric Patients with Bone and Soft Tissue Sarcomas: A Pilot Retrospective Study (SarcoPed)

Abstract: Background: We evaluated nutritional and sarcopenia status and their clinical impact in pediatric patients affected by bone and soft tissue sarcomas. Methods: Body mass index (BMI), prognostic nutritional index (PNI), and total psoas muscle area (tPMA) at diagnosis and after 12 months were analyzed. tPMA was measured from single cross-sectional computed tomography (CT) images at L4–L5. Age-specific and sex-specific tPMA Z-scores were retrieved from an online calculator. Results: A total of 21 patients were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
(52 reference statements)
1
11
0
5
Order By: Relevance
“…Though malnutrition was a significant complication in this population, with a prevalence of 30% at diagnosis increased to 38% three months later, there was no impact of malnutrition on survival outcomes [ 35 ]. Likewise, a study on 139 children with Ewing sarcoma and osteosarcoma reported high proportions of malnutrition 2 years after treatment initiation (43% of osteosarcoma and 25% of Ewing sarcoma) [ 36 ]; again, malnutrition had non-significant effects on survival outcomes. A more recent study assessed the prognostic effect of sarcopenia, defined by the BMI-z score, the prognostic nutritional index (PNI), and the total psoas muscle area (tPMA), on the survival of children with bone and soft tissue sarcomas [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Though malnutrition was a significant complication in this population, with a prevalence of 30% at diagnosis increased to 38% three months later, there was no impact of malnutrition on survival outcomes [ 35 ]. Likewise, a study on 139 children with Ewing sarcoma and osteosarcoma reported high proportions of malnutrition 2 years after treatment initiation (43% of osteosarcoma and 25% of Ewing sarcoma) [ 36 ]; again, malnutrition had non-significant effects on survival outcomes. A more recent study assessed the prognostic effect of sarcopenia, defined by the BMI-z score, the prognostic nutritional index (PNI), and the total psoas muscle area (tPMA), on the survival of children with bone and soft tissue sarcomas [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many reports have shown that sarcopenia is closely related to the prognosis of patients with various malignant tumors. 3,[6][7][8][9][10][11]13,[19][20][21] However, different pathological types of sarcomas are not identical in treatment and prognosis, so we conducted a study on the exact pathological type of sarcomas and drew relevant conclusions. Meanwhile, the effect of sarcopenia on the post-surgical outcomes of patients with liposarcoma undergoing en bloc compartment resection has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have shown that sarcopenia is closely related to the prognosis of patients with various malignant tumors. [ 3 , 6 11 , 13 , 19 21 ] However, different pathological types of sarcomas are not identical in treatment and prognosis, so we conducted a study on the exact pathological type of sarcomas and drew relevant conclusions. Meanwhile, the effect of sarcopenia on the post-surgical outcomes of patients with liposarcoma undergoing en bloc compartment resection has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, some publications explored the relationship between sarcopenia and clinical outcomes among patients with sarcoma; one reported that there was no relationship between psoas cross-sectional area and clinical outcomes after soft tissue resection [6]. The others demonstrated that sarcopenia was independently associated with poorer long-term prognosis in sarcoma [3,[7][8][9][10][11], and lower psoas muscle attenuation was associated with higher mortality [8,12]. The advanced studies showed that sarcopenia is associated with prognostic parameters in advanced or metastatic STS and first-line therapy response [13].…”
Section: Introductionmentioning
confidence: 99%